THE ROLE OF TRADITIONAL KNOWLEDGE DIGITAL LIBRARY IN PROTECTION OF INDIAN TRADITIONAL KNOWLEDGE: A CRITICAL ANALYSIS - Manjari Chandra; Shabran, Rohit P (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research analyzes the pivotal role of Traditional Knowledge Digital Libraries (TKDLs) in safeguarding Indian traditional knowledge, critically analyzing their impact on preservation, accessibility, and legal protection. Examining the key features and functionalities of existing TKDLs, we assess their effectiveness in documenting and disseminating traditional knowledge. The study delves into the legal and policy frameworks at national and international levels, evaluating their support and potential hindrances to utilizing TKDLs for protection. Additionally, we explore the extent to which these digital repositories empower indigenous communities and practitioners while respecting cultural sensitivities and intellectual property rights. Challenges in digitization and management of traditional knowledge are scrutinized, seeking solutions for ethical considerations. The research also gauges stakeholder perspectives, including those of indigenous communities, policymakers, researchers, and legal experts, to understand the perceived effectiveness and relevance of TKDLs. This paper covers a number of topics related to the Traditional Knowledge Digital Library of India (TKDL), such as its contribution to the preservation of traditional knowledge, safeguarding and disseminating traditional knowledge, the database’s current status, advantages of TKDL, instances of bio-piracy of Indian traditional knowledge, and the organization’s most notable accomplishments in this area.